Voršilky v Čechách a jejich pojetí veřejné prospěšnosti - Macková, Marie (Univerzita Pardubice, 2008)
Ursulines were one of two women regular orders admitted as publicly convenient at the times of the restriction of monasteries in Bohemia during the reign of Josef II. However, their public convenience was not based on the enlightened principles. They were allowed to provide education at the end of the 16th century. Ursulines should follow the decrees of Trent and work on internal restoration of catholicism. These ideas were transformed in the second half of the 18th century and then in the 19th century. In fact, the Ursulines continued to be a religious order that ran girl schools. The slowly changing social conditions perceived this kind of service and accepted it differently during the course of history.
Keywords: voršilky; ženské řeholní řády; veřejná prospěšnost; historický vývoj